Model Pembelajaran Missouri Mathematics Poject Terhadap Kemampuan Pemecahan Masalah Matematis Ditinjau dari Self Confidence Siswa - Hartono Hartono; Niasika Nurul Huda; Iwit Prihatin (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2020)
The purpose of this research, to see the difference between the model of Missouri Mathematics Project learning and conventional learning on mathematical problem-solving abilities in terms of students' self-confidence. The method used in this research is an experimental with kind of a Quasi-Experimental, and the research design is a 2x3 factorial design. The population in this study were all students of class XI MIPA of SMA Negeri 6 Pontianak consist of four classes, with class XI MIPA III and XI MIPA IV samples selected by the Cluster Random Sampling technique. Based on the analysis of variance of two paths with unequal cells it is concluded that: 1) The Missouri Mathematics Project learning model provides better mathematical problem-solving abilities compared to conventional learning in the matrix material. 2) Students who have high, medium and low self-confidence have no difference in the ability to solve mathematical problems in the matrix material. 3) In each learning model, students with high, medium and low self-confidence do not provide differences in mathematical problem solving between self -confidence found in themselves. 4) At each level of students' self-confidence, the Missouri Mathematics Project learning model provides better mathematical problem-solving skills than conventional learning.